2005
DOI: 10.1002/jcla.20069
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of endostatin in patients with idiopathic pulmonary fibrosis

Abstract: Endostatin is an angiogenesis inhibitor that is an endogenously produced proteolytic fragment of type XVIII collagen. Serum levels of endostatin have been studied extensively in patients with malignant diseases. Recently, elevated serum endostatin levels were observed in patients with systemic sclerosis accompanying pulmonary fibrosis. To determine whether elevated serum endostatin can be observed in patients with idiopathic pulmonary fibrosis (IPF), we measured serum levels of endostatin in 69 patients with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Elevated levels of serum and BALF endostatin are seen in fibrotic disorders such as IPF and SSc (1618). Endostatin was increased in IPF patients with severe respiratory dysfunction and in SSc patients with pulmonary fibrosis and severe skin fibrosis compared to patients without those clinical manifestations (1618).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of serum and BALF endostatin are seen in fibrotic disorders such as IPF and SSc (1618). Endostatin was increased in IPF patients with severe respiratory dysfunction and in SSc patients with pulmonary fibrosis and severe skin fibrosis compared to patients without those clinical manifestations (1618).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that endostatin is 2 to 20 times higher in serum and/or bronchoalveolar lavage fluid (BALF) from patients with idiopathic pulmonary fibrosis (IPF) and SSc-associated pulmonary fibrosis than from normal subjects (1618). Because cytokines and signaling molecules implicated in angiogenesis development have also been identified in purpose, we evaluated the effect of endostatin and endostatin-derived peptides on the generation of fibrosis in vitro using primary human fibroblasts, ex vivo using human skin, and in vivo in TGF-β– and bleomycin-induced dermal and pulmonary fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Endostar, a novel modified human recombinant endostatin with an additional nine amino acids purified from Escherichia coli , was approved for the treatment of non–small cell lung cancer in combination with other chemotherapy drugs in China in 2005 [37]. Elevated levels of endostatin are observed in the BALF and serum of IPF patients, especially those with severe respiratory dysfunction, compared to patients without these clinical manifestations [38,39]. A previous study [40] showed that recombinant endostatin inhibited dermal fibrosis in an ex vivo human skin model, and a peptide derived from endostatin prevented dermal and lung fibrosis induced by BLM in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…John et al (1999) purified different circulating endostatin forms from human blood ultrafiltrate (hemofiltrate). Changes in the level of the circulating endostatin have been observed both under physiological and pathological conditions (Gu et al 2004;Seko et al 2004;Sumi et al 2005) and may lead under certain Fig. 10 CLSM of the simultaneous detection of (a) endostatin and (b) a-smooth muscle actin within aortae of mice housed for 3 weeks at hypoxia.…”
Section: Discussionmentioning
confidence: 99%